Depression, anxiety and stress in adult population from 20 to 40 years old in Centla municipality of Frontera Tabasco, Mexico - Maas Góngora , Lucely (2023)
Objective: To identify the degree of depression, anxiety and stress in the adult population aged 20 to 40 years in Centla, municipality of Frontera Tabasco, Mexico. Method: Quantitative descriptive cross-sectional research carried out on 222 subjects between the ages of 20 and 40 through non-probability sampling for convenience given the accessibility of the participants. The DASS-21 Scale was used, which was designed to measure negative emotional states such as depression, anxiety and stress, the data were processed through the statistical program SPSS V23. Main results: It was identified that anxiety-related symptoms predominate (56,3%), followed by depressive symptoms (54,1%) and finally stress symptoms (48,2%). When considering only the participants who manifested symptoms, it was possible to identify that the moderate category predominates in 32,5% of the participants with depressive symptoms and 32,0% with anxiety symptoms, in addition to the fact that 34,4% are located with mild stress symptoms. Conclusion: The study shows that there is an alteration in the emotional states of individuals, which could limit individual, family and social development, in addition to representing an area of ​​opportunity for health professionals in the promotion and care of health. mental.